Extending Character Education (PPK) as the Basis for Curriculum Management to Improve the Quality of Learning at SDN 2 Rimo - Bancin, Rika Rosari; Amini, Amini; Akrim, Akrim (LP2M STIT Palapa Nusantara, 2024)
Character is the